Development of Co/Co9S8 metallic nanowire anchored on N-doped CNTs through the pyrolysis of melamine for overall water splitting. (1st February 2021) - Ashok, Anchu; Kumar, Anand; Ponraj, Janarthanan; Mansour, Said A
Highlights: Co/Co9 S8 nanowires encapsulated in MWCNT were synthesized using melamine pyrolysis. Melamine act as the source of both carbon and nitrogen. Presence of sulfur in Co dramatically improves the electrocatalytic activity. Carbon bamboo nanotubes (CBNT) and MWCNT structures evolve during the pyrolysis. Co/Co9 S8 /CNT generated 10 mAcm −2 water splitting current at 1.5 V cell voltage. Abstract: Herein, we report the successful synthesis of Co9 S8 metal-sulfide nanowire trapped in multi walled carbon nanotube (MWCNT), which was subsequently found to be an effective catalyst for water splitting. Melamine pyrolysis together with a Co precursor results in MWCNTs, with the addition of sulfur during synthesis enhancing the surface area, pore size, and oxygen vacancy defects in the nanotubes. The hierarchical structure of Co/Co9 S8 /CNT products boosted the electron mobility and mass transport for both the oxygen evolution (OER) and hydrogen evolution reaction (HER) in alkaline medium. Doping the catalyst surface with Pyridinic-N atoms, Graphitic-N atoms and thioamide S-atoms dramatically improved the bifunctional electrocatalytic performance by lowering the overpotentials for OER and HER reactions. The Co/Co9 S8 /CNT generated a current density of 10 mAcm −2 water-splitting current by applying a cell voltage of only 1.5 V. Further, Co/Co9 S8 /CNT showed excellent stability. The mechanism of Co8 S9 nanowire formation in the MWCNT was also investigated.